Association of Cigarette Smoke Exposure with Tuberculosis in Children: A Literature Review - Yunitama, Alifa Agil Dhillu; Asmara, Desilva Zahra; Balqis, Aida; Zahra, Adinda Aisyah; Shoom, Listyani Mubshiro Shom; Fauziyah, Nida Faradisa (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study purpose is to discuss cigarette smoke exposure as a risk factor for tuberculosis in children. Methodology: This study is a literature review, conducted through an extensive search of international literature using the BMC, Nature, PubMed, Scopus, and JEPH databases. The inclusion criteria: 1) Published in the last 5 years; 2) Sought for retrieval; 3) Abstract recording to the theme; 4) Free full text; 5) Content of the journal match the theme. Results: The filtering processes produced 15 articles that were relevant to this study. 13 studies stated that there was a remarkable relationship between smoking and TB in children. Cigarette smoke diminishes the effector cytokine response and hampers the ability of infected human macrophages to contain mycobacteria, increasing susceptibility to TB. Applications/Originality/Value: This study can be use for a reference regarding the influence of cigarette smoke exposure to tuberculosis in children.